2011
DOI: 10.1371/journal.pone.0021069
|View full text |Cite
|
Sign up to set email alerts
|

Shared Epitope Alleles Remain A Risk Factor for Anti-Citrullinated Proteins Antibody (ACPA) – Positive Rheumatoid Arthritis in Three Asian Ethnic Groups

Abstract: BackgroundTo investigate the associations between HLA-DRB1 shared epitope (SE) alleles and rheumatoid arthritis in subsets of rheumatoid arthritis defined by autoantibodies in three Asian populations from Malaysia.Methods1,079 rheumatoid arthritis patients and 1,470 healthy controls were included in the study. Levels of antibodies to citrullinated proteins (ACPA) and rheumatoid factors were assessed and the PCR-SSO method was used for HLA-DRB1 genotyping.ResultsThe proportion of ACPA positivity among Malay, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 29 publications
6
53
0
1
Order By: Relevance
“…The relationship of the DRB1*0401 alleles with the predisposition to the disease in our study was in compliance with the studies conducted on Spanish (13), Greek (14) and Caucasian (15) populations, as well as the populations in various regions in Turkey (11,12). Similarly, the relationship of the DRB1*0408 subtype with the predisposition to RA in our study was in line with other studies conducted (15). However, the DRB1*01, DRB1*04, DRB1*0404 and DRB1*0405 alleles were not observed to have a statistically significant relationship with the disease in our region, although the frequency of these alleles was higher in patients with RA.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship of the DRB1*0401 alleles with the predisposition to the disease in our study was in compliance with the studies conducted on Spanish (13), Greek (14) and Caucasian (15) populations, as well as the populations in various regions in Turkey (11,12). Similarly, the relationship of the DRB1*0408 subtype with the predisposition to RA in our study was in line with other studies conducted (15). However, the DRB1*01, DRB1*04, DRB1*0404 and DRB1*0405 alleles were not observed to have a statistically significant relationship with the disease in our region, although the frequency of these alleles was higher in patients with RA.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies reported these alleles unequivocally associated with immune-related diseases [70][74]. The possibility cannot be ruled out that these alleles may be either susceptibility genes or linkage disequilibrium with other susceptibility genes contributing to the etiology of PD.…”
Section: Discussionmentioning
confidence: 99%
“…In Asian populations there are important differences in the prevalence of the various HLA-DRB1 SE alleles,16 17 and the RA-risk allele *0901, which lacks the SE motif, is found more commonly 16 18 19. Xue et al 20 found that the SE was associated with RA but not with ACPA production in a small Chinese RA cohort, whereas such associations have been reported in Malaysian, Chinese and Japanese patients 21 22. In a mixed Malaysian population, smoking, the SE and the interaction between them, only conferred risk for ACPA-positive RA 23.…”
Section: Introductionmentioning
confidence: 99%